"We Do Not Have It, and We Do Not Want It": Women, Power, and Convent Reform in Florence - Evangelisti, Silvia (The sixteenth century journal, 2003)
This article discusses the introduction of Tridentine reform in Tuscan convents, in particular the implementation of enclosure and the subsequent reactions of nuns. In Tuscany, Tridentine laws coexisted with disciplinary measures sponsored by the church and the state concerning the government of convents. Enclosure laws were enforced through negotiations within local communities involving both ecclesiastical and state authorities and the nuns, who expressed their discontent and sometimes refused to live under lock and key. Evidence from various sources, including convent writings by nuns, suggests that they feared physical segregation because it would limit their economic welfare, their religious and social visibility, and above all their capacity to exert authority and power over their own community. When Tridentine reform made headway within Tuscany, enclosure was still a much-debated notion, and was not simply the universal model for female religious life supported by the Catholic church.